Tipe Gaya Belajar Siswa Madrasah Ibtidaiyah Dalam Menghafal Al Qur’an di Yogyakarta - Ahmad Shofiyuddin Ichsan (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to determine the types of learning style of Madrasah Ibtidaiyah (MI) students in memorizing the Qur'an. The type of this research is qualitative research using Case Study strategy in two schools, namely MI Negeri 1 Bantul and MI YAPPI Gubukrubuh Gunungkidul. For data collection, this study uses three methods, namely observation, in-depth interviews, and documentation. The results of the study explained that there are at least four learning styles, namely 1). Visual style of students memorizing the Qur'an, 2). Aural style of students memorizing the Qur'an, 3). Kinesthetic style of students memorizing the Qur'an, and 4). Social style of students memorizing the Qur’an. Keywords: Types of Learning Style, Madrasah Ibtidaiyah, Memorizing the Qur'an